2022
DOI: 10.1108/ejm-06-2020-0431
|View full text |Cite
|
Sign up to set email alerts
|

Salesperson moral identity and value co-creation

Abstract: Purpose The purpose of this study is to examine the role of salesperson moral identity centrality in value co-creation. This study identified and tested an extended identity-based formation process of selling orientation, customer orientation and value co-creation. This was accomplished by examining the role of inclusion of others in the self and circle of moral regard in the mechanism through which moral identity centrality impacts selling orientation, customer orientation and value co-creation, taking into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…Similarly, earlier studies found how customers participate in brand advocacy for social causes, with the individuals with inherent tendencies having a solid emotional bond with the brand and perceiving it as their identity (Delpechitre et al, 2018;Itani et al, 2022). Likewise, customers exhibiting a higher brand engagement are more inclined to showcase customer citizenship behavior (Nicola et al, 2023).…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, earlier studies found how customers participate in brand advocacy for social causes, with the individuals with inherent tendencies having a solid emotional bond with the brand and perceiving it as their identity (Delpechitre et al, 2018;Itani et al, 2022). Likewise, customers exhibiting a higher brand engagement are more inclined to showcase customer citizenship behavior (Nicola et al, 2023).…”
Section: Discussionmentioning
confidence: 81%
“…This study emphasizes for the first time the market ethics shaping of college students and on-the-job marketers through network marketing training. When the moral identity of marketers is improved, they can reduce sales orientation and increase customer orientation, thereby improving sales performance (Itani et al, 2022). However, the present research found that the shaping mechanism of marketing ethics is different under different trainee identities and training forms.…”
Section: Discussionmentioning
confidence: 99%
“…For business-to-business (B2B) salespeople, value cocreation (Itani et al , 2022) and cross/upselling behaviors (Johnson and Friend, 2015) are critical growth strategies. Specifically, value cocreation refers to purposeful engagement and collaboration with customers to jointly produce and enhance value for customers (Itani et al , 2022; Ranjan and Read, 2016), whereas cross/upselling behaviors refer to efforts directed at generating more value from customers by upgrading them to more profitable offerings (Johnson and Friend, 2015). Given the complex and dynamic nature of the B2B sales environment, salespeople need to continuously search for opportunities to enhance their abilities to create value for and extract value from customers (Rangarajan et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In general, while a few prior studies have explored how salespeople can use internal networking, exploratory navigation and internal selling as mechanisms to identify, nurture and channel internal organizational resources (Liu et al , 2020; Nguyen et al , 2018; Plouffe et al , 2016; Steward et al , 2010), there are significant gaps in the systematic research on salespeople’s entrepreneurial acquisition of resources that are external to the organization, such as social capital. In particular, although sales researchers have highlighted that the utilization of digital tools and technologies can enable salespeople to form professional relationships and expand social networks (Itani et al , 2022; Rangarajan et al , 2021), studies are yet to offer compelling evidence on how salespeople’s social media use helps in the acquisition of social capital through those relationships and networks spanning organizational boundaries. Correspondingly, by leveraging emergent perspectives from the resource acquisition literature (Maritan and Peteraf, 2011; Martens et al , 2007) and recent research on the utilization of social media by salespeople (Minsky and Quesenberry, 2016), we develop and test a framework that demonstrates how B2B salespeople’s use of social media enhances their social capital, which, in turn, contributes to their value creation activities.…”
Section: Introductionmentioning
confidence: 99%